An Investigation of Changes in Identity in Japanese Native Speakers as they Acquire English Language Proficiency - Foley, David Brian , Jr. (Journal of International Scholars Conference - EDUCATION/SOCIAL SCIENCES, 2016)
Japan has a highly effective national education system, but English proficiency is one of its weakest points. The cultural harmony of the Japanese people poses a natural barrier to the integration of outside languacultures. This study is an investigation into identity changes inherent to switching from Japanese to English. The findings herein will illuminate the source of Japan’s problem with learning English and better equip Japanese authorities to hire teachers, inform curriculum, and utilize resources. Data for this study will be collected by interviewing Japanese people who have gained a high level of English proficiency. Data will be analyzed through epoching, bracketing, and imaginative variation and conclusions will be discussed in the form of a narrative. I expect to find that the identity challenge posed to Japanese students of English will be great and require a lot more attention than it is currently being given by the Japanese authorities.